Fabrication of 6FDA-based composite membranes loaded with MIL-125 (Ti) for CO2/CH4 separation - Suhaimi, N.H. (Institute of Physics Publishing, 2020)
Carbon dioxide (CO2 ) separation is necessary for natural gas purification to enhance the calorific value of methane gas (CH4 ), besides reducing the corrosion risk in pipelines with the presence of water or moisture. This work focuses on the development of new combination of composite membrane materials containing titanium-based metal organic frameworks (MOFs) and 6FDA-based polymer for CO2 and CH4 gases permeation. The composite membranes were successfully fabricated by incorporating 0.5, 1.0, 3.0 and 5.0 wt of MIL-125 (Ti) fillers into 6FDA-durene polymer by using solvent evaporation method. The resultant fillers and composite membranes were characterized by using different analytical tools including XRD, FESEM and EDX. Then, the permeability test was conducted by using single gas of CO2 and CH4. The results showed that composite membrane loaded with 5wt of MIL-125(Ti) showed the highest CO2 permeability of 814.9 Barrer, and CO2/CH4 ideal selectivity of 18.1 compared to pure 6FDA-durene membrane with CO2 permeability of 510.3 Barrer and CO2/CH4 ideal selectivity of 8.6. It was found that the incorporation of fillers, MIL-125 (Ti) into 6FDA-durene polymer matrix led to the enhancement of gas permeation performance due to good compatibility between fillers and polymer matrix. Besides, the presence of organic ligand in MIL-125 (Ti) filler has potentially reduced the interfacial voids between the filler and polymer. Â© Published under licence by IOP Publishing Ltd.